PENINGKATAN HASIL BELAJAR IPA TENTANG SIKLUS AIR MELALUI MODEL PICTURE AND PICTURE PADA SISWA KELAS V UPTD SDI NAIKOTEN 1 KUPANG - Koroh, Taty R.; Adoe, Treesly Y. N; Tukan, Damianus S. (Journal of Character and ELementary Education, 2023)
This research aims to improve the learning achievement of class V students on theme 9 Water Cycle at SDI Naikoten 1 Kupang. The type of research used is classroom action research consisting of four steps, namely: design, implementation, observation, and test and evaluation. This research was attended by 25 fifth-grade students, 15 male students and 10 female students. Data collection was carried out through observation and experimental techniques. The information obtained is then processed and analyzed using qualitative descriptive analysis techniques. This research was conducted at SDI Naikoten 1 Kupang. Data is collected through observation and tests. The information obtained was then analyzed using qualitative descriptive analysis techniques. The research results showed that in cycle I, only 5 out of 25 students (around 20%) completed the initial test. Meanwhile, around 80% or 20 students failed to complete the assignment at that stage. In cycle II, 24 out of 25 students (around 96%) successfully completed the assignment, while only 1 student (around 4%) did not successfully complete the assignment. Based on the results of this research, it can be concluded that the application of image-based and experimental learning models in class 9 can improve the learning outcomes of class V students at SDI Naikoten 1 Kupang.